Analysis of the Effect of Safety Equipment and Ship Maintenance on Risk Mitigation and Implications on Shipping Safety of Ncvs Ship in West Kalimantan - Agustina, Sella; Simanjuntak, Marihot; Rosmayana, Rosmayana; Herawati, Susi (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the impact of Safety Equipment and ship Maintenance on risk mitigation and its implications for the safety of navigation of Non-Convention Vessel Standard (NCVS) ships in West Kalimantan. The main issue addressed in this study is how the completeness and readiness of Safety Equipment, as well as the quality of ship maintenance, can minimize potential risks and support navigational safety. This research uses a descriptive quantitative approach with a cross-sectional design. The population of the study consists of all NCVS crew members in the West Kalimantan region, specifically the Rasau Jaya-Teluk Batang route, with a sample size of 140 respondents selected using saturated sampling. The data were analyzed using a closed-ended Likert scale questionnaire. Hypothesis testing was performed using SmartPLS 4 software to examine the relationships and effects between variables. The results indicate that Safety Equipment and ship Maintenance have a significant impact on risk mitigation and indirectly contribute positively to navigational safety. These findings have important implications for NCVS operational management, emphasizing the need for closer attention to the compliance of Safety Equipment standards and the regular preventive maintenance schedules to improve navigational safety in the West Kalimantan work area